Small-Scale Variability in the Soil Microbial Community Structure in a Semideveloped Farm in Zambia. (15th March 2018) - Hamamoto, Toru; Chirwa, Meki; Nyambe, Imasiku; Uchida, Yoshitaka
Abstract : The conversion of natural lands into agricultural lands can lead to changes in the soil microbial community structure which, in turn, can affect soil functions. However, few studies have examined the effect of land use changes on the soil microbial community structure in sub-Saharan Africa. Therefore, the aim of this research was to investigate the relationships among soil characteristics and microbial communities in natural and agricultural ecosystems in a semideveloped lowland farm in the central region of Zambia, within which small-scale wetlands had been partly developed as watermelon ( Citrullus lanatus ) and/or maize ( Zea mays ) farms. We sampled soils from four different land use types within this farm: "native forest, " "grassland, " "watermelon farm, " and "maize farm." We found that the land use type had a significant effect on the soil bacterial community structure at the class level, with the class Bacilli having significantly higher relative abundances in the forest sites and Gammaproteobacteria having significantly higher relative abundances in the maize sites than in the other land use types. These findings indicate that these bacterial classes may be sensitive to changes in soil ecosystems, and so further studies are required to investigate microbial indicators for the sustainable development of wetlands in sub-Saharan Africa.